Integrasi Agrowisata dan UMKM dalam Digital Promotion Menggunakan Virtual Tour di Desa Pematang Gajah - Nabila Suniyyah; Febri Heryansah; Daniel Arsa; Nur Fadilah Oktarivia; Baldy Antila Putra; Mukhtada Billah Nst (JITU, 2024)
The increasing role of digital technology in tourism and local economic development, especially in villages with agrotourism potential and SMEs, has led to the use of virtual tours as an effective tool for promoting both sectors. This research aims to fill the gap in the literature by examining the integration of virtual tours to promote agrotourism and local SMEs in Desa Pematang Gajah. Despite its significant potential, the village faces challenges in reaching a wider audience and maximizing digital marketing. This study uses a qualitative approach with descriptive analysis and action research methods to design, implement, and evaluate a virtual tour system that integrates both sectors. The results indicate that the introduction of digital innovation, including a website and virtual tour feature, has effectively enhanced the promotion of the village's agrotourism and SME products. Training for local stakeholders, such as SMEs and village officials, played a crucial role in the success of the project, demonstrating increased digital skills and a broader market reach. This research contributes to the understanding of how virtual tours can bridge the gap in promoting agrotourism and SMEs, especially in rural areas with limited technological infrastructure.